High performance porous graphene nanoribbons electrodes synthesized via hydrogen plasma and modified by Pt-Ru nanoclusters for charge storage and methanol oxidation. (10th November 2018) - Torabi, Mostafa; Karimi Shervedani, Reza; Amini, Akbar
Abstract: Porous graphene nanoribbons are synthesized via an effective and template-free method based on introducing of carbon black (CB) into the graphene oxide (GO) layers, and then, thermal exfoliation under hydrogen plasma (H2 ) stream (PGNRs/CB). The nanocomposites are transferred onto the glassy carbon electrode surface (GCE) and tested directly for charge storage intentions or further modified with Pt-Ru alloy nanoclusters and examined for electrooxidation of methanol . The physicochemical characteristics and electrochemical activities of composites are studied by several surface techniques and electrochemical methods. A remarkable specific capacitance (223.0 F g −1 at 1.0 A g −1 ) is achieved for PGNRs/CB electrode, compared with 137.2 and 67.6 F g −1 values obtained for porous graphene nanoribbons (PGNRs) and graphene nanosheets (GNs-Ar) formed in the presence of H2 plasma and pure argon streams, respectively. The capacitance retention remained at more than 91% even after 5000 cycles. The supercapacitive behavior and excellent durability achieved for PGNRs/CB materials are attributed to the (i) large surface area of PGNRs obtained by annealing in H2 plasma, and thus, the increased ion accessibility of graphene system, and (ii) stability against the restacking of the PGNRs achieved in the presence of CB. In addition, the GCE-PGNRs/CB was successfully used as a favorable support and further modified with Pt-Ru alloy nanoclusters via electrodeposition. The GCE-PGNRs/CB/Pt-Ru showed an excellent electrocatalytic activity, high resistance against poisoning effect of CO and good stability toward oxidation of methanol. The experimental results are presented and discussed, regarding charge storage and electrocatalytic oxidation of methanol. Graphical abstract: Highlights: Porous graphene nanoribbons/carbon black, 1062 m 2 g –1, thermally fabricated in H2 -plasma. The PGNRs/CB electrode showed a large specific capacitance, 223.0 F g −1 at 1.0 A g −1 . GC-PGNRs/CB was successfully modified with Pt-Ru metal alloy nanocluster. GC-PGNRs/CB/Pt-Ru electrode showed excellent activity & stability for CH3 OH oxidation.